2018
DOI: 10.1096/fj.201700970
|View full text |Cite
|
Sign up to set email alerts
|

L1 coupling to ankyrin and the spectrin‐actin cytoskeleton modulates ethanol inhibition of L1 adhesion and ethanol teratogenesis

Abstract: Ethanol causes fetal alcohol spectrum disorders (FASDs) partly by inhibiting cell adhesion mediated by the L1 neural cell adhesion molecule. Ethanol interacts with an alcohol binding pocket in the L1 extracellular domain (ECD), and dephosphorylation of S1248 in the L1 cytoplasmic domain (CD) renders L1 adhesion insensitive to inhibition by ethanol (L1 insensitive). The mechanism underlying this inside-out signaling is unknown. Here we show that phosphorylation of the human L1-CD at S1152, Y1176, S1181, and S12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…For example, the highly sialylated form of NCAM is overexpressed after ethanol exposure but the NCAM 180 and NCAM 140 isoforms appear down-regulated in a rat model (137). Other studies in animal models (mice and rats) have shown down-regulation of L1 following ethanol exposure (134,138).…”
Section: Synaptogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the highly sialylated form of NCAM is overexpressed after ethanol exposure but the NCAM 180 and NCAM 140 isoforms appear down-regulated in a rat model (137). Other studies in animal models (mice and rats) have shown down-regulation of L1 following ethanol exposure (134,138).…”
Section: Synaptogenesismentioning
confidence: 98%
“…PAE affects the expression levels of synaptic proteins such as synapsin 1 and of other proteins of the pre-synaptic (GAP-43, synaptophysin, synaptotagmin) or post-synaptic machinery (MAP 2 and neurogranin). Moreover, ethanol interferes with the function of adhesion molecules such as NCAM (in chick embryo model) ( 133 ) and L1 (in mouse model) ( 134 ) involved in cell-cell interactions. During the neural processes of migration and morphogenesis, both proteins are involved in the organization and function of synaptic networks, which determine neuronal plasticity.…”
Section: Developmental Stages Of the Fetal Brainmentioning
confidence: 99%
“…76,[80][81][82][83] Alcohol disrupts neural cell migration and axonal pathfinding by blocking cell adhesion and axon outgrowth mediated by the L1 neural cell adhesion molecule. 84 Of note, mutations in the human L1 gene cause dysgenesis of the corpus callosum, hydrocephalus, and cerebellar dysplasia, mirroring some of the neuropathological abnormalities of FAS. Alcohol also alters craniofacial and brain development by disrupting PDGFRA and its downstream signaling elements, PI3K and mTOR.…”
Section: Pathophysiologymentioning
confidence: 99%
“…85 Genetic polymorphisms in PDGFRA and in genes that regulate L1 sensitivity to ethanol are associated with craniofacial and brain dysmorphology in humans. 84,85 Developmental Course FASD has not been well studied in adults and the phenotype is older adults is unknown. Some adults received their diagnoses during childhood; however, the high prevalence of FASD and high rates of misdiagnosis in children 10 suggest that FASD is often undiagnosed in adults.…”
Section: Pathophysiologymentioning
confidence: 99%
“…67 Also, it has been recently documented that L1 coupling to ankyrin and therefore to the spectrin-actin skeleton modulates ethanol inhibition of L1 adhesion and ethanol teratogenesis. 80 Furthermore, aII-spectrin interacts with the protein 14-3-3, which is engaged in neuronal migration and synaptic plasticity. This interaction works as a positive/negative switch in NCAM-dependent neurite outgrowth.…”
Section: Cell Adhesion and Spreadingmentioning
confidence: 99%